Relations among Density-based Equicontinuities - Zhang, Yue; Lu, Tianxiu; Gong, Siyu (European Journal of Applied Sciences, 2026)
Equicontinuity is a regularity condition for characterizing global orbital stability in topological dynamical systems (t.d.s.). This study investigates the relationship between four kinds of density-based equicontinuity in t.d.s., and examines their inhibitory effects on chaos. Under the framework of minimality, density-equicontinuity, mean equicontinuity, density- -equicontinuity, and almost density-equicontinuity are obtained to be equivalent to each other. And density-equicontinuity is incompatible with chaos.